Identification of Potent Bioassay Guided Terpenoid and Glycoside Root Fractions of Astragalus candolleanus against Clinically Significant Bacterial Strains - Nagarajan, Kandasamy; Ghai, Roma; Varshney, Garima; Grover, Parul; Genovese, Carlo; D’Angeli, Floriana; Goel, Richa; Prasad, Thota; Kalaivani, Muthusamy; Teotia, Anil Kumar (International Journal of Microbiology, 2022)
Antibiotic resistance represents one of the biggest challenges, and there is an urgent need for plant-based antimicrobial agents that enable managing this crisis effectively. In this work, we aimed to investigate the antibacterial activity of Astragalus candolleanus (A. candolleanus) hydromethanolic root extract against Gram-positive (Bacillus subtilis and Staphylococcus aureus) and Gram-negative (Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Kocuria rhizophila) strains by the cup-plate method. The root was powdered and extracted with 70% methanol by cold maceration for 5 days. Preliminary phytochemical screening was performed with different solvents in the order of increasing polarity. Pure compounds were isolated by column chromatography and were characterized through liquid chromatography-mass spectrometry. Targeted predictions of the isolated compounds were also studied using Swiss Target prediction software and prediction of activity spectra for substances. The extract showed a broad zone of inhibition against pathogenic bacteria. Four pure compounds were isolated, of which a novel terpenoid compound has been identified as stemmadenine along with scillirosidin, cephalotaxine, and myxoxanthophyll. The structures of the isolated phytoconstituents were elucidated by spectral analysis. The four pure components isolated from the roots of A. candolleanus are suggested to be effective against tested pathogens. Overall results of drug design suggest that myxoxanthophyll is a promising bioactive compound endowed with antibacterial activity.